(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the level of knowledge regarding Standard Precautions (SP) among healthcare workers and identify associated factors at Ha Dong General Hospital in 2025. Methods: A cross-sectional study was conducted among 721 healthcare workers at Ha Dong General Hospital in 2025. Data were collected through face-to-face interviews using a structured questionnaire. Logistic regression analysis was used to determine factors associated with SP knowledge. Results: The proportion of healthcare workers with adequate knowledge of Standard Precautions was 79.6%. Female participants were more likely to have adequate knowledge than males (OR = 1.7; p = 0.01). Compared with physicians, healthcare workers in other professional categories had significantly lower odds of adequate knowledge (OR = 0.3; p < 0.001). Participants with educational qualifications below university level were less likely to achieve adequate knowledge than those with a university degree or higher (OR = 0.6; p = 0.002). No significant associations were found between SP knowledge and age, years of work experience, or participation in training programs. Conclusion: Knowledge of Standard Precautions among healthcare workers was relatively good; however, about 20% did not achieve the required level. Strengthening regular training, knowledge updates, and supervision, particularly for staff with lower educational attainment and professional groups with lower knowledge levels, may improve compliance with Standard Precautions and enhance patient safety.